The 722 Slavic Manuscript from the Library of the Romanian Academy in Bucharest and the Polish Chronicle - Biliarsky, Ivan (Studia Ceranea, 2026)
This article is devoted to a brief Cyrillic text, known as “Polish Chronicle”. Presently kept in the library of the Romanian Academy in Bucharest, it was included in a 16th century Tetraevangelium (BAR, Ms. sl. 722). Only a small part of the text has survived, as the rest of the folio was cut off. It is a local chronicle from Galicia (then in the Polish-Lithuanian Commonwealth) recording various events, most of which pertain to Polish-Tatar relations. From the surviving fragment, one may conclude that it is a kind of sylva rerum – a form of chronicle writing which was popular in that region and during this era. Although the text is brief and poorly preserved, I believe that researchers should be familiar with it.